SynGAP moves out of the core of the postsynaptic density upon depolarization - Yang, Yijung (2011)
SynGAP is a Ras GTPase activating protein present at the postsynaptic density (PSD) in quantities matching those of the core scaffold protein PSD-95. SynGAP is reported to inhibit synaptic accumulation of AMPA receptors. Here, we characterize by immunogold electron microscopy the distribution of SynGAP at the PSD under basal and depolarizing conditions in rat hippocampal neuronal cultures. The PSD core, extending up to 40 nm from the postsynaptic membrane, typically shows label for SynGAP, while half of the synapses exhibit additional labeling in a zone 40–120 nm from the postsynaptic membrane. Upon depolarization with high K(+), labeling for SynGAP significantly decreases at the core of the PSD and concomitantly increases at the 40–120 nm zone. Under the same depolarization conditions, label for PSD-95, the presumed binding partner of SynGAP, does not change its localization at the PSD. Depolarization-induced redistribution of SynGAP is reversible and also occurs upon application of NMDA. Activity-induced movement of SynGAP could vacate sites in the PSD core allowing other elements to bind to these sites, such as transmembrane AMPA receptor regulatory proteins, and simultaneously facilitate access of SynGAP to CaMKII and Ras, elements of a regulatory cascade.